ANALISIS REKAMAN MUSIK DENGAN PENDEKATAN DIGITAL - Fransiskus Rendy, B. Com, M.A.B, Fransiskus Rendy, B. Com, M.A.B (Akademi Komunikasi SAE Indonesia, 2022)
There are as yet numerous who use sound from unrecorded music video accounts for music. This is the basic interest of analysts to lead research on the examination of the keep interaction with advanced techniques in KM Studio Pontianak. This exploration utilizes enlightening examination strategy with subjective structure utilizing study with work overview type or work (Occupations Review). This study was directed in six phases in view of the stages in the recording system and the investigation of the recording. The investigation of the recording shows the objectivity of the openness of the recurrence and its reach in the sound system space and subjectivity in light of the assessment of each asset who paid attention to the keep in this review